EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs - Smolen, Josef S. (2022)
Funding Information: This study was funded by European League Against Rheumatism. Publisher Copyright: © Author(s) (or their employer(s)) 2022. No commercial re-use. See rights and permissions. Published by BMJ.